Identidade e representação: a construção da identidade nas referências visuais de ambientes de redes digitais - Stein, Helga (2007)
The goal of this project is to research how virtual communities such as orkut and flickr are molding new identity and self-presentation parameters. The present project takes as study object photographic self-portraits and its associated representation forms. In self-portraits the relation between the observer and who is observed has blurred limits, demanding a body with a special quality: a body in process. This new body of multiple identities is reconfigured intermittently assuming new behaviors facing new technologies, requiring a new configuration of world. It is expected that digital images reflects these processes by being capable of reconfiguring itself. We show through representation the world we live in. However, contemporary world faces a crisis of representation, knowledge and great complexity in matters of subjectivity production. The images that are produced and propagated throughout a historical period are indications of a specific way of thinking. In virtual communities such as orkut, multiply and flickr, the use of images (especially self-portraits) creates a dynamic process of identification and differentiation of the individual. The identity, however, is influenced by interaction processes (comments of community members, number or visitors). So, the self-portraits are redefined as by the demands of specific sociability matters (the success, in terms of numbers of visitors and content of the commentaries). The influence of new technologies in the way we understand the construction of identity will be interrogated through specific readings and through artistic projects that deals with the concepts presented in the research